Postoperative Long-Term Outcomes and Independent Risk Factors of Non-Small-Cell Lung Cancer Patients With Propofol versus Sevoflurane Anesthesia: A Retrospective Cohort Study - Zhenglian Gao; Zhenglian Gao; Jian Xu; Mark Coburn; Daqing Ma; Kun Wang; Kun Wang (Frontiers Media S.A., 2022)
Background: Existing studies have shown that the relationship between anesthetic agents and non-small-cell lung cancer (NSCLC) prognosis remains controversial. Therefore, this retrospective cohort study was designed to investigate the effects of propofol or sevoflurane anesthesia on the long-term oncologic outcomes of NSCLC patients.Methods: We identified 1,778 eligible patients (propofol-based total intravenous anesthesia (TIVA) group, n = 686; sevoflurane-based inhalation anesthesia (INHA) group, n = 1,092) out of 2,388 patients undergoing elective NSCLC surgery from June 2013 to June 2016 in the Harbin Medical University Cancer Hospital. The primary endpoints were five-year overall survival and recurrence-free survival. The secondary endpoints were independent risk factors of cancer recurrence or all-cause mortality. The data were analyzed with propensity score matching, Kaplan-Meier survival, and Cox multivariate analyses as appropriate.Results: After propensity score matching, there were 672 patients in each group. The median follow-up period was 69 months (interquartile range: 68-70 months) for all patients. Five-year overall survival was 75.7% (95% confidence interval (CI) 72.4-79.1) in the TIVA group and 71.8% (68.4-75.4) in the INHA group (p = 0.160) (hazard ratio (HR), 0.86; 95% CI, 0.70-1.06; p = 0.158), and five-year recurrence-free survival was 68.5% (65.0-72.2) and 62.7% (59.1-66.5 (p = 0.108) (HR, 0.90; 95% CI, 0.75-1.08; p = 0.253), respectively. Subgroup analyses showed there were no significant difference in the overall survival or recurrence-free survival between the two groups in each TNM stage of NSCLC. The independent risk factors included age ≥60 years, male, blood transfusion, segmental/wedge resection and pneumonectomy, thoracotomy, postoperative complications, lung adenocarcinoma, TNM stages, high CEA and CYFRA211 levels, and postoperative radiotherapy.Conclusions: Our data indicated no difference between the propofol-based TIVA and sevoflurane-based INHA in terms of five-year overall survival and recurrence-free survival after NSCLC surgery.